Adherence to neuroleptic treatment in psychiatric practices: A retrospective study of 55 practices with more than 5000 bipolar and schizophrenic patients in Germany. (February 2020) - Bohlken, Jens; Konrad, Marcel; Kostev, Karel
Highlights: The study included 2870 schizophrenia (SP) and 2327 bipolar disorder (BP) patients. The mean medication procession ratio (MPR) was 65% in BP and 60% in SP. The share of patients with an optimal MPR value differed greatly between practices. Psychiatrists play an important role in the compliance of SP and BP patients. Abstract: Background: The aim of this study was to investigate the effect that treating physicians have on the compliance of their psychiatric (schizophrenia (SP) and bipolar disorder (BP)) patients. Methods: This retrospective study was based on data from the Disease Analyzer database (IQVIA). It included 2870 SP and 2327 BD patients who had received at least two neuroleptic prescriptions from 55 psychiatric practices between January 2016 and December 2018. The average proportion of days covered (PDC) per patient was calculated. Patients were considered adherent if their PDC was greater than or equal to 80%. Practice adherence was considered high if at least 70% of patients in the practice of interest were adherent. Results: The mean PDC was 59.8% (SD: 13.9%) in SP and 65.0% (SD: 11.5%) in BD patients. The share of patients with an optimal PDC value (≥80%) differed considerably between practices (between 28% and 92% for SP and between 33% and 92% for BP). The prevalence of practices with high adherence was lower for schizophrenia than for bipolar disorder (21.9% versus 45.5%). Conclusion: Psychiatrists play an important role in the compliance of SP and BP patients treated with neuroleptics.